Building New Hope for Drug Addicts through an Educational Ecosystem: A Rehabilitation Study of Drug Abuse Victims at the NAPZA Islamic Boarding School - Subiyantoro, Subiyantoro; Rohmadani, Zahro Varisna; Marwadi, Ferika Aulia; Ardiansyah, Adnan (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Drug abuse is a multidimensional phenomenon that produces extensive impacts on health, psychological well-being, and social integration. Conventional rehabilitation models often struggle to provide long-term, holistic environments that support sustained recovery. This study explores pesantren-based rehabilitation as an alternative recovery ecosystem by examining the rehabilitation process for drug abuse victims at Pondok Pesantren Al-Islamy, Kulon Progo, Yogyakarta. Employing a qualitative intrinsic case study Design, data were collected through in-depth interviews, participant observation, and document analysis involving rehabilitated students, kyais, teachers, and rehabilitation companions. Data were analyzed using an interactive qualitative study model within a multidisciplinary theoretical framework integrating ecological, psychological, educational, sociological, and neurobiological perspectives. The findings reveal that pesantren-based rehabilitation operates as a structured socio-religious ecosystem that facilitates behavioral change, cognitive and emotional transformation, spiritual development, and identity reconstruction. Key mechanisms include strict daily routines, collective religious practices, social modeling, and community-based learning, which together support self-regulation and reduce relapse risk. The pesantren environment fosters the development of recovery capital by providing strong social support, spiritual meaning, and communal belonging, enabling rehabilitated individuals to transition from stigmatized identities as drug users to socially legitimate identities as santri. However, the study also identifies challenges related to post-rehabilitation reintegration, highlighting the need for sustained support beyond the pesantren setting. This study concludes that pesantren-based rehabilitation represents an effective, culturally grounded, and holistic model for long-term addiction recovery. By integrating educational structure, spiritual guidance, and community support, pesantren function as transformative recovery ecosystems that offer significant implications for addiction rehabilitation policy and practice in Indonesia.